2013
DOI: 10.1007/s12017-013-8250-1
|View full text |Cite
|
Sign up to set email alerts
|

The CLU Gene rs11136000 Variant is Significantly Associated with Alzheimer’s Disease in Caucasian and Asian Populations

Abstract: Large-scale genomewide association studies have reported that the CLU rs11136000 polymorphism is significantly associated with Alzheimer's disease (AD) in people of Caucasian ancestry. Recently, this association was investigated in Asian populations (Chinese, Japanese, and Korean). However, these studies reported either a weak association or no association between the rs11136000 polymorphism and AD. We believe that this discrepancy may be caused by the relatively small sample size of the previous studies and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 24 publications
0
34
1
1
Order By: Relevance
“…Subsequent replication efforts have provided confirmation of the signal in ZCWPW1 (Ruiz et al, 2014) as well as evidence of association at TRIP4 . Multiple validation studies (studies examining associations among different ethnicities) in Southeast Asian populations have demonstrated associations at many of these loci: CLU (Komatsu et al, 2011; Liu et al, 2014; Yu et al, 2013), CR1 (Jin et al, 2012), PICALM (Chung et al, 2013; Liu et al, 2013; Miyashita et al, 2013), BIN1 (Liu et al, 2013; Miyashita et al, 2013), and the MS4A gene cluster (Deng et al, 2012; Tan et al, 2013). …”
Section: Genetics Of Alzheimer Disease: Late-onset Alzheimer Disease mentioning
confidence: 99%
“…Subsequent replication efforts have provided confirmation of the signal in ZCWPW1 (Ruiz et al, 2014) as well as evidence of association at TRIP4 . Multiple validation studies (studies examining associations among different ethnicities) in Southeast Asian populations have demonstrated associations at many of these loci: CLU (Komatsu et al, 2011; Liu et al, 2014; Yu et al, 2013), CR1 (Jin et al, 2012), PICALM (Chung et al, 2013; Liu et al, 2013; Miyashita et al, 2013), BIN1 (Liu et al, 2013; Miyashita et al, 2013), and the MS4A gene cluster (Deng et al, 2012; Tan et al, 2013). …”
Section: Genetics Of Alzheimer Disease: Late-onset Alzheimer Disease mentioning
confidence: 99%
“…In addition to the rs6656401 and rs3818361 polymorphisms, we previously analyzed PICALM rs3851179, BIN1 rs744373, and CLU rs11136000 and rs2279590 polymorphisms [1,[6][7][8][9]. We found that there was no significant genetic heterogeneity of these polymorphisms in Asian and European populations.…”
Section: Discussionmentioning
confidence: 99%
“…We found that there was no significant genetic heterogeneity of these polymorphisms in Asian and European populations. We further analyzed relatively largescale samples and reported significant association between these common variants and AD in Asian populations [1,[6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations